Prevalence of Potential Drug-Drug Interaction Risk among Chronic Kidney Disease Patients in a Spanish Hospital - Gracia Santos-Díaz; Ana María Pérez-Pico; Miguel Ángel Suárez-Santisteban; Vanesa García-Bernalt; Raquel Mayordomo; Pedro Dorado (MDPI AG, 2020)
Chronic kidney disease (CKD) is a major health problem worldwide and, in Spain, it is present in 15.1% of individuals. CKD is frequently associated with some comorbidities and patients need to be prescribed multiple medications. Polypharmacy increases the risk of adverse drug reactions (ADRs). There are no published studies evaluating the prevalence of potential drug-drug interactions (pDDIs) among CKD patients in any European country. This study was aimed to determine the prevalence, pattern, and factors associated with pDDIs among CKD patients using a drug interactions program. An observational cross-sectional study was carried out at Plasencia Hospital, located in Spain. Data were collected among patients with CKD diagnoses and pDDIs were assessed by the Lexicomp® Drug Interactions platform. Data were obtained from 112 CKD patients. A total number of 957 prescribed medications were acknowledged, and 928 pDDIs were identified in 91% of patients. Age and concomitant drugs were significantly associated with the number of pDDIs (p < 0.05). According to the results, the use of programs for the determination of pDDIs (such as Lexicomp®) is recommended in the clinical practice of CKD patients in order to avoid serious adverse effects, as is paying attention to contraindicated drug combinations.